Quality Assurance in Classroom Delivery and Management. - Uwaezuoke, Martha-Rose Ifeoma; Morah , Bibian Ukamaka (International Journal of Educational Management, 2022)
Formal education entails inculcating knowledge, skills, societal norms and values to the learners which are intended to lead to positive perpetual behaviour modification of the recipients. This kind of education cannot take place in a vacuity, it is carried out in a school setting which has many buildings, and one of such is the classroom. Classroom is the fulcrum of the school. This is because; it is in the classroom that actual teaching and learning take place. It is where the content of the school curriculum is imbued with the students’ under the guidance of the teacher. It is for this singular reason that classroom should be prioritized among other structures that make up the school by making it furnished, comfy and roomy hence vivacious, under the management of the teacher, whose activities must from time to time be monitored to ensure that there is no deviation from the stipulated guide lines, if it must achieve what it is set out to accomplish. Quality and functional education no doubt promotes national growth and development. Consequently, the paper focused on the concept of quality assurance, classroom furniture, class size, quality teacher, access to recommended text books as well as classroom management that would foster sound education that is capable of producing intellectual properties that could be rated anywhere in the world.